Novel Neuroimaging Biomarker for Sleep Quality in Insomnia Disorder: A Hypothalamus Resting State Study - Ding, Shuang; Gao, Lijuan; Kukun, Hanjiaerbieke; Ai, Kai; Zhao, Wei; Xie, Chao; Wang, Yunling (Frontiers in Neuroscience, 2021)
Despite striking progress in the understanding of the neurobiology of primary insomnia (PI), about 40% of PI patients do not reach sustained remission with the primary treatments. It is necessary to reveal novel neuroimaging biomarkers for sleep quality in PI. The hypothalamus has a central role in sleep–wake regulation by communicating with different brain regions. However, the functional implications of hypothalamus circuitry with other brain areas remains largely unknown in PI. It may be speculated that the dysfunctional in hypothalamus circuitry is involved in the pathogenesis of PI. Thus, we investigated the different network organizations of bilateral hypothalamus during resting-state between 26 PI patients and 28 healthy controls (HC). Correlation analysis has been carried out to link the neuroimaging findings and Pittsburgh Sleep Quality Index (PSQI) scores. Group comparisons revealed that the resting-state functional connectivity (RSFC) between the left hypothalamic and a few brain regions, including the medial prefrontal cortex (mPFC)andpallidum, was significantly higher in PI compared with HC. Right inferior temporal cortex showed reduced RSFC with the left hypothalamus. No significant different RSFC between PI and HC were detected for the right hypothalamus. Positive correlations with PSQI scores were observed for RSFC strength between the left hypothalamus and bilateral mPFC (left: r=0.2985, p=0.0393; right: r=0.3723, p=0.0056). Similarly, the RSFC strength between the right hypothalamus and bilateral mPFC (left: r=0.3980, p=0.0029; right: r=0.2972, p=0.0291) also showed significant positive correlations with PSQI scores. In conclusion, we revealed novel neuroimaging biomarker for sleep quality, i.e. the RSFC strength of the hypothalamus-mPFC pathway. Consistent with the hyperarousal model of PI, our results shed new insights into the implications of the hyper-connection within hypothalamus circuits in the pathology of the PI.